A "Struggle of Life or Death": Han and Uyghur Insecurities on China's North-West Frontier. (9th June 2020) - Tobin, David
Abstract: In July 2009, nearly 200 people were killed in ethnically targeted mass violence between Turkic-speaking Muslim Uyghurs and Han Chinese in Urumqi, overshadowing the 60th anniversary of the founding of the People's Republic of China (PRC). How have ethnic relations between Han and Uyghurs descended into mass violence among ordinary people? This paper argues that the party-state exacerbates ethnic tensions between Han and Uyghurs through ethnocentric security narratives. These narratives frame China's identity as being under threat from Turkic enemies within who are supported by Islamic terrorists and Western "enemies of China" from outside. Discourse analysis of official texts, participant-observation of security practices, and interviews with Han and Uyghurs reveal the interplay between official identity discourses and everyday security practices before, during and after the violence. Since July 2009, one official solution to ethnic violence has been the construction of a shared multi-ethnic identity, officially described as a "zero-sum political struggle of life or death." However, Han-centric conceptualizations of ethnic unity promote Han chauvinism and portray the Uyghur as a security threat. The party-state thus creates hierarchical ethnic relations that exacerbate both Han and Uyghur insecurities and contribute to spirals of violence. China's extra-judicial internment camps in Xinjiang are the logical conclusions of the ethnocentric insecurity cycles analysed in this article.